Foreclosure and Profit Shifting With Partial Vertical Ownership - Matthias Hunold; Vasilisa Werner (Journal of Economics & Management Strategy, 2024)
We demonstrate that the incentives of firms that partially own their suppliers or customers to foreclose rivals depend on how the partial owner can extract profit from the target. Compared to a fully vertically integrated firm, a partial owner may obtain only a share of the target's profit but may have significant influence over the target's strategy. We show that the incentives for customer and input foreclosure can be higher, equal, or even lower with partial ownership than with a vertical merger, depending on how the protection of minority shareholders and transfer price regulations affect the scope for profit extraction.
Keywords: 330; foreclosure; minority shareholdings; partial ownership; profit shifting; vertical integration